2015
DOI: 10.1186/s12987-015-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

The intrathecal, polyspecific antiviral immune response in neurosarcoidosis, acute disseminated encephalomyelitis and autoimmune encephalitis compared to multiple sclerosis in a tertiary hospital cohort

Abstract: BackgroundA polyspecific, intrathecal humoral immune response against the neurotropic viruses, measles, rubella and varicella zoster virus, called “MRZ reaction” (MRZR), is present in the majority of patients with multiple sclerosis (MS). Neurosarcoidosis (NS) and acute disseminated encephalomyelitis (ADEM) are important clinical differential diagnoses of MS. Autoimmune encephalitis (AIE) represents a well characterized autoimmune CNS disorder with intrathecal antibody synthesis. The aim of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 25 publications
2
29
1
3
Order By: Relevance
“…Moreover, it would be relevant to investigate both the IgG1 allotype restriction and the intrathecal polyspecific anti‐viral reaction in MS patients with other genetic backgrounds, such as Asian/Mongoloid populations, in which there has been a chromosomal crossover, leading to another combination of IgG1 allotypes in a proportion of the individuals. Here, we found similar levels of intrathecal virus‐specific antibodies as previous studies 4, 24, 25. Thus, it is unlikely that selection bias has influenced our results.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, it would be relevant to investigate both the IgG1 allotype restriction and the intrathecal polyspecific anti‐viral reaction in MS patients with other genetic backgrounds, such as Asian/Mongoloid populations, in which there has been a chromosomal crossover, leading to another combination of IgG1 allotypes in a proportion of the individuals. Here, we found similar levels of intrathecal virus‐specific antibodies as previous studies 4, 24, 25. Thus, it is unlikely that selection bias has influenced our results.…”
Section: Discussionsupporting
confidence: 90%
“…However, a relapsing disease course suggestive for MS was not reported by the patient. Additionally, the cMRI Swanton criteria for dissemination in time and space were not fulfilled and the MRZ reaction, a polyspecific, intrathecal humoral immune response against neurotropic agents (measles, rubella, and varicella zoster virus), which is possibly the most specific available CSF marker for MS (26), was also negative. Therefore, we were not able to diagnose MS or an early stage of this disease although previous studies showed an association between BD and MS (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of Guillain-Barré (GBS) patients (total n = 56, Table 3) with the number of simultaneously-increased antibody titers in blood (total n = 22 antibody species analyzed) 8 . The fit with a Gaussian function shows a mean connectivity of five antibody species out of IgG 19 and IgM 3 class antibodies against 19 infectious microbes.…”
Section: Normal Antibody Dynamics In Bloodmentioning
confidence: 98%
“…There is a discontinuity between an infection or vaccination and the recognition of an autoimmune disease or multisymptom illnesses of a few weeks to two months 3,4,5,6 after the initiating event. In MS, as well, there is no development such as starting with an acute demyelinating meningoencephalitis and slowly becoming an MS 19,25 . The youngest patient, investigated at age of five years 25 , already had the complete set of immune reactions, like a complete MRZ antibody reaction 25 .…”
Section: Causation In Chronic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation